8‐C‐(E‐phenylethenyl)quercetin from onion/beef soup induces autophagic cell death in colon cancer cells through ERK activation. Issue 2 (11th November 2016) - Zhao, Yueliang; Fan, Daming; Zheng, Zong‐Ping; Li, Edmund T.S.; Chen, Feng; Cheng, Ka‐Wing; Wang, Mingfu
Abstract : 8‐ C ‐( E ‐phenylethenyl)quercetin (8‐ CEPQ ), a novel quercetin derivative, could be formed in onion/beef soup. 8‐ CEPQ inhibits colon cancer cell growth by inducing autophagic cell death through extracellular signal‐regulated kinase (ERK) activation. Abstract : Scope: Quercetin, a flavonoid, widely distributed in edible fruits and vegetables, was reported to effectively inhibit 2‐amino‐1‐methyl‐6‐phenylimidazo[4, 5‐b]pyridine (PhIP) formation in a food model (roast beef patties) with itself being converted into a novel compound 8‐ C ‐( E ‐phenylethenyl)quercetin (8‐ CEPQ ). Here we investigated whether 8‐ CEPQ could be formed in a real food system, and tested its anticancer activity in human colon cancer cell lines. Methods and results: LC‐MS was applied for the determination of 8‐ CEPQ formation in onion/beef soup. Anticancer activity of 8‐ CEPQ was evaluated by using cell viability assay and flow cytometry. Results showed that 8‐ CEPQ suppressed proliferation and caused G2 phase arrest in colon cancer cells. Based on immunofluorescent staining assay, western blot assay, and RNA knockdown data, we found that 8‐ CEPQ did not cause apoptotic cell death. Instead, it induced autophagic cell death. Moreover, treatment with 8‐ CEPQ induced phosphorylation of extracellular signal‐regulated kinase (ERK). Inhibition of ERK phosphorylation by the mitogen‐activated protein kinase kinase (MEK)/ERK inhibitor U0126 attenuated 8‐ CEPQ ‐induced autophagy and reversed 8‐ CEPQ ‐mediated cell growth inhibition. Conclusion: Our results demonstrate that 8‐ CEPQ, a novel quercetin derivative, could be formed in onion/beef soup. 8‐ CEPQ inhibited colon cancer cell growth by inducing autophagic cell death through ERK activation.